DISKURSUS HAK EKSKLUSIF INDIKASI GEOGRAFIS ATAS PENGHAPUSAN MEREK TERDAFTAR DALAM PERLINDUNGAN HUKUM HAK KEKAYAAN INTELEKTUAL - Kurniaman Telaumbanua; Endang Pandamdari (Jurnal De Lege Ferenda Trisakti, 2024)
Both trademarks and geographical indications are legal instruments that govern market communication about a product. Trademarks indicate the commercial origin of goods or services, while geographical indications signify geographical origin. Both also legally provide exclusive rights to use certain words or symbols. This research finds that trademarks and geographical indications are unique, non-interchangeable tools, and it is possible for legislation to protect both simultaneously; therefore, they are not in conflict but rather seen as harmonious tools. Specifically, in the implementation of laws in Indonesia, the implementation of Geographical Indications (GI) is given a higher status than that of registered trademarks. Explicitly, the Law of the Republic of Indonesia Number 20 of 2016 on Trademarks and Geographical Indications, Article 72 paragraph (7), governs the removal of registered trademarks at the initiative, one of which is based on having similarity in essence and/or in entirety with a Geographical Indication. Therefore, it is necessary to develop legal formulations that can accommodate both trademark and geographical indication holders because both possess exclusive rights.